PENGEMBANGAN E-LKPD MENGGUNAKAN LIVEWORKSHEETS PADA MATERI SISTEM PENCERNAAN MANUSIA - Adelia Angeline Hafidzah; Elly Sukmanasa; Ade Wijaya (STKIP Subang, 2024)
Adelia Angeline Hafidzah. 037120062. Development of E-LKPD using Liveworksheets on Human Digestive System Material. This study aims to determine the development of E-LKPD using liveworksheets in class V of Kedung Badak 2 State Elementary School, Bogor City, and to determine the feasibility of E-LKPD using liveworksheets on the learning process. The method used in this study is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research subject of class V A students of Kedung Badak 2 State Elementary School, Bogor City, consisting of 21 students, the research was carried out in the even semester of the 2023/2024 school year. This research begins with a needs analysis, making an E-LKPD design, validation by experts, revising the E-LKPD, and after that the E-LKPD trial, and evaluation. The results of the study show that E-LKPD using Liveworksheets on Human Digestive System Materials has met the criteria of being very feasible to use by obtaining a percentage of 98.5% from media experts, 100% from linguists, and 94% from material experts. Meanwhile, the trial conducted on 21 students in class V received a response with a percentage of 90.1% and a teacher response with a percentage of 98%. Based on these data, it can be concluded that E-LKPD using Liveworksheets is very feasible to be used by students and teachers as teaching materials on the human digestive system in grade V of elementary school.